Creation of Personas by End-Users in Alcohol and Drugs Abuse Rehabilitation - de Souza, Paula Maia; Neris, Vânia Paula de Almeida; Proença, Fernando Roberto; Garcia, Franco Eusébio (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC); 2021: Anais do XX Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais, 2021)
Personas is a consolidated technique to support design solutions and designers have successfully used the technique to build digital solutions in the health domain. There are several studies in the literature that examine the creation of Personas with the participation of health professionals. However, since patients are generally only information providers, there have been few studies of patients being involved by acting as creators of Personas for therapeutic reasons. This paper investigates the co-creation of Personas by patients undergoing rehabilitation for alcohol and drugs abuse. The activity was part of a larger project in which patients adopted the SemTh approach to co-create therapeutic digital games. Twenty-one patients, one healthcare professional and four computing professionals took part in the Personas creation workshop and seven personas were created. By conducting a qualitative analysis, in this paper, we were able to determine eleven lessons learned from the process.